Nijmegen breakage syndrome cells fail to induce the p53-mediated DNA damage response following exposure to ionizing radiation. - Jongmans, W (1997)
The functionality of the p53-mediated pathway, activated in response to DNA damage, has been assessed in primary fibroblast cell cultures and Epstein-Barr virus-transformed lymphoblastoid cell lines derived from Nijmegen breakage syndrome (NBS) patients. This autosomal recessive disease is characterized by microcephaly, growth and mental retardation, chromosomal instability, radiosensitivity, and high cancer incidence. The recent mapping of the NBS gene to chromosome 8q21 demonstrates that NBS is genetically distinct from ataxia telangiectasia (AT). Changes in p53 protein levels were significantly reduced and delayed in all the NBS fibroblast cell cultures and lymphoblastoid cell lines examined compared to normal cultures over a 4-h period postirradiation (5 Gy). The transcriptional activation of p21(WAF1/CIP1) mRNA was also lower in 12 NBS fibroblast cultures examined. In agreement with an abrogated p53 function, NBS cells exposed to ionizing radiation show an abnormal cell cycle arrest at G1-S and a prolonged accumulation of cells in the G2 phase. In contrast, exposure to the alkylating agent methyl methanesulfonate results in similar increases of p53 and p21(WAF1/CIP1) mRNA in both cell types. The ATM gene transcript was found to be expressed at similar levels in NBS and normal cells, whereas it was strongly reduced in the AT homozygote cells examined. These results suggest that the ATM gene product cannot substitute for that of the NBS gene in the signaling of cellular damage produced by ionizing radiation and that both are involved in the activation of p53. The suboptimal p53-mediated response could contribute to the high cancer risk and radiosensitivity seen in NBS patients.